Heus tu! Promittis ad cenam, nec venis? Dicitur ius! The Relationship between Pliny Ep. 1.15 and Several Carmina Catulli - Hogenmüller, Boris (Classica et Mediaevalia, 2021)
Various studies have already shown that Catullus is one of many authors whose work Pliny the Younger preferred to read and to whom he often referred in his letters. An interesting example of this intertextual reference is found in Ep. 1.15. It is obvious that Pliny refers to the specific contents and motifs from three different poems of Catullus, which the addressee of the letter should easily have been reminded of when reading the letter. That Catullus’ poems are the underlying (or superordinate) hyper-texts to which Pliny refers is what this paper aims to prove.